PENERAPAN METODE ANALYTIC HIERARCHY PROCESS DALAM PENGUKURAN KINERJA KARYAWAN PADA IBI DARMAJAYA - Sushanty Saleh (IIB Darmajaya, 2013)
Lecturer PNS is part of private college as a lecturer helped for Kopertis. Of course it is expected to be an example for other lecturer in each university in implementation for Tridarma High Education or other performance indicator suits for Kopertis rules. Assessment lecturer PNS can be done easily and automatically by using Decision Support System Model suits with criteria determinate by Kopertis, especially Kopertis region II. The model is used Aanalytic Hhierarchy Process Method. Implementation of this model is done through the following phases: data collecting, determinate main criteria and sub criteria in Assessment lecturer, weighting criteria and sub criteria, determinate priorities and implementation by using expert choice. According the application Analytic Hierarchy Process Method can be known that criteria has been defined are education teaching, research, society service and support component.Keyword: performance, AHP, expert choice